The Lemons Problem in a Labor Market with Intrinsic Motivation: When Higher Salaries Pay Worse Workers - Francesca Barigozzi; Nadia Burani; Davide Raggi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
We study the Lemons Problem when workers have private information on both their skills and their intrinsic motivation for the job offered by firms in the labor market. We first show that, when workers are motivated, inefficiencies due to adverse selection are mitigated. More interestingly, depending on the association between productivity and motivation, higher salaries affect the pool of candidates in three possible ways: they can attract (i) more skilled but less motivated applicants, as expected; (ii) more skilled and more motivated applicants; (iii) less skilled and less motivated applicants. The last two counterintuitive effects can only occur when a positive correlation exists between productivity and motivation. Our results are relevant in the policy debate on whether it is possible to improve the quality of workers in vocational markets by changing their wage rate and reconcile the different empirical evidence provided so far on motivated workers such as public servants, teachers, health professionals and, politicians.
Keywords: J24; J21; J3; D82; 330